Formation of a Novel Antagonistic Bacterial Combination to Enhance Biocontrol for Cucumber Fusarium Wilt - Fan Yang; Xin Wang; Huayan Jiang; Xiaoke Chang; Weiwei Chen; Gongyao Shi; Baoming Tian; Qiuju Yao (Microorganisms)
Paenibacillus polymyxa strain PJH16, isolated and tested by our team, suppresses cucumber Fusarium wilt as an efficient biocontrol agent. For further investigation, the strain has been combined with two other Bacillus strains (Bacillus velezensis VJH504 and Bacillus subtilis JNF2) to enhance biocontrol ability, which formed high-efficiency microbial agents in the current study. The methodological target taken is based on achieving the optimal growth conditions of the combined microbial agents; hence, the medium composition and culture conditions were optimized through a single-factor test, orthogonal test and response surface methodology. Following this, the effectiveness of the microbial combination was assessed through pot experiments, which provided a theoretical foundation for the synthesis of microbial flora to significantly control cucumber Fusarium wilt. The results showed excellent compatibility, proving suitable for the proliferation and growth of Paenibacillus polymyxa PJH16, Bacillus velezensis VJH504, and Bacillus subtilis JNF2 strains together, specifically, when the inoculation amounts were adjusted to 4% of each. Using the single-factor test and orthogonal test analysis, the optimum composition of culture medium for the composite strain was identified as 3% glucose as the optimal carbon source, 2% yeast extract powder as the preferred nitrogen source, and 1% dipotassium hydrogen phosphate as the most suitable inorganic salt. Furthermore, the optical density (OD600) of the composite strain solution reached its highest level at 3.16 under the following culture conditions: inoculation volume of 200 µL, 171 rpm culture speed, 21.6 h culture time, 30 °C cultural temperature, and an initial pH of 7.0. The pot experiment demonstrated that the mixed bacterial solution achieved a relative control efficacy of 93.4% against cucumber Fusarium wilt, which was significantly superior to that of single- strain or pesticide treatment, and also promoted cucumber growth. In summary, the microbial flora synthesized by the three Bacillus strains displayed a high bacterial concentration, following the optimization of culture conditions, and exerted remarkable control and growth-promoting effects on cucumber Fusarium wilt. This finding holds great significance for future developments of composite microbial agents.